Inversion of uterus with sub mucus fundal fibroid with secondary infection and shock: a rare case report - Raja Kumari, K. S.; S, Radha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In inversion of uterus, fundus of uterus comes down in reverse direction, through the cervix, exposing endometrial surface. Diagnosis of inversion of uterus is often difficult. Cervix is drawn up and vaginal portion of cervix would not be palpable. The most common disorder in differential diagnosis is a prolapsed fibroid. Acute inversion commonly occurs in 3rd stage of labor, and is an acute obstetric emergency. In our case, inversion of uterus occurred in non -puerperal period, in menopausal woman, due to sub mucous fundal fibroid, with acute presentation. Patient was in shock with pyrexia, and successfully managed surgically, after treating infection and shock.